Compensation of distortions in VSC-based DC-AC power systems using a modified vector control method - AKPOLAT, ALPER NABİ (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Offshore wind farms are always connected to onshore alternating current (AC) power systems using direct current (DC) submarine cables through a DC-AC voltage source converter station. In most cases, nonlinear loads are located on the AC side of the station. The distortion caused by such loads tends to flow into the AC system due to its low impedance, negatively impacting power quality and raising the power losses. This paper presents a novel vector control method (VCM) for the DC-AC station to simultaneously deliver the power demanded by the AC side and act as a shunt active power filter to suppress distortions. In this scope, the conventional VCM is further modified by developing several control loops with proper control and power parameters to obtain a sufficiently wide bandwidth. Additionally, the performance of three different types of low pass filters (LPF) is investigated due to the significant role of LPF in the success of the proposed method. Simulation and experimental outcomes are provided to validate the effectiveness of the proposed method
Keywords: Power quality; Voltage source converter; Harmonic compensation; AC-DC station; PERFORMANCE IMPROVEMENT; LCL FILTER; VOLTAGE; DESIGN; SYNCHRONIZATION; INVERTER; PLL